Intrapopulation analysis of longitudinal lifespan in Caenorhabditis elegans identifies W09D10.4 as a novel AMPK-associated healthspan shortening factor - Yoshio Nakano; Masataka Moriuchi; Yutaro Fukushima; Kyotaro Hayashi; Mary Ann Suico; Hirofumi Kai; Go Koutaki; Tsuyoshi Shuto (Elsevier, 2021)
Caenorhabditis elegans is a model organism widely used for longevity studies. Current advances have been made in the methods that allow automated monitoring of C. elegans behavior. However, ordinary manual assays as well as automated methods have yet to achieve qualitative whole-life analysis of C. elegans longevity based on intrapopulation variation. Here, we utilized live-cell analysis system to determine the parameters of nematode lifespans. Image-based superposition method enabled to determine not only frailty in worms, but also to measure individual and longitudinal lifespan, healthspan, and frailspan. Notably, k-means clustering via principal component analysis revealed four clusters with distinct longevity patterns in wild-type C. elegans. Physiological relevance of clustering was confirmed by assays with pharmacological and/or genetic manipulation of AMP-activated protein kinase (AMPK), a crucial regulator of healthspan. Finally, we focused on W09D10.4 among the possible regulators extracted by integrative expression analysis with existing data sets. Importantly, W09D10.4 knockdown increased the high-healthspan populations only in the presence of AMPK, suggesting that W09D10.4 is a novel AMPK-associated healthspan shortening factor in C. elegans. Overall, the study establishes a novel platform of longitudinal lifespan in C. elegans, which is user-friendly, and may be a useful pharmacological tool to identify healthspan modulatory factors.